2020
DOI: 10.1101/2020.04.20.051011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limited SARS-CoV-2 diversity within hosts and following passage in cell culture

Abstract: Since the first reports of pneumonia associated with a novel coronavirus (COVID-19) emerged in Wuhan, Hubei province, China, there have been considerable efforts to sequence the causative virus, SARS-CoV-2 (also referred to as hCoV-19) and to make viral genomic information available quickly on shared repositories. As of 30 March 2020, 7,680 consensus sequences have been shared on GISAID, the principal repository for SARS-CoV-2 genetic information. These sequences are primarily consensus sequences from clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Haploflow identified two strains in nine samples, consistent with in-sample variation [36][37][38] . The assembled contigs were assessed with QUAST 39 using the Wuhan-Hu-1 isolate strain (RefSeq NC_045512.2) as reference genome.…”
Section: After Correcting For Pcr Amplification and Sequencing Errorssupporting
confidence: 54%
“…Haploflow identified two strains in nine samples, consistent with in-sample variation [36][37][38] . The assembled contigs were assessed with QUAST 39 using the Wuhan-Hu-1 isolate strain (RefSeq NC_045512.2) as reference genome.…”
Section: After Correcting For Pcr Amplification and Sequencing Errorssupporting
confidence: 54%
“…The 21 KZN whole genomes (20 KRISP and one NICD) were assigned to SARS-CoV-2 sub-lineages according to the nomenclature proposed and lineage classification obtained from >5000 genomes analyzed by Rambaut et al ( Rambaut et al, 2020 ). Given uncertainties pertaining to the low diversity of this virus ( Moreno et al, 2020 ), we restricted lineage assignment to the four most prominent subgroups (A, B, B·1 and B·2). Of the 21 KZN isolates being investigated in the present study, one was assigned to lineage B ( KRISP-006 ) and one to sub-lineage B·2 ( KRISP-002 ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Even if several studies report variants found at frequencies below 0.1 (25,27,37-39) only a few evaluated the confidence of such calls (26,40). We found that the number of variants with VAF>0.1 detected in samples with at least 1000 g.c.p.r is similar between contemporaneous samples and increases with time since the start of the outbreak, as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts to genotype the Zika virus using amplicon-based approaches suggested that the fraction at which a variant can be confidently separated from technical noise is no lower than 3% even when sufficient input material, sequencing depth and replicates are used (24). However, some of the variants considered in the analysis of SARS-CoV-2 intra-host genome variability were reported at lower fractions (25-27). Furthermore, data generated by different laboratories might contain specific biases, compromising their direct comparison and the validity of downstream analysis (11,12).…”
Section: Introductionmentioning
confidence: 99%